If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-8+2-4=12-8x+14
We move all terms to the left:
x-8+2-4-(12-8x+14)=0
We add all the numbers together, and all the variables
x-(-8x+26)-8+2-4=0
We add all the numbers together, and all the variables
x-(-8x+26)-10=0
We get rid of parentheses
x+8x-26-10=0
We add all the numbers together, and all the variables
9x-36=0
We move all terms containing x to the left, all other terms to the right
9x=36
x=36/9
x=4
| 3+4(c)=15 | | -12=-9+8x | | (3z-3)=6.6 | | (z=10)/9=2 | | -6=3x+11 | | 150m-100m+47,750=50,500-200m | | 1.8^n=3 | | 3+1=d | | 3x-41=2x+14 | | 150m-100+47,750=50,500-200m | | 8x-(-15+3-17)+18=2x-(-5) | | 27+73=100+d*100−365 | | 150m-100+47,750=50,500-200 | | 131-u=254 | | 1/4x+8=-6 | | 1/7x=-16 | | 2x-3÷5=-13 | | 6/9.4=4.2/x | | 4(×+3)=3(3x-1) | | 2n+35=107 | | 0.25x+38.61=C | | (3x-1)/4=(4x-2)/5 | | 70-5x=320 | | 3x-1)/4=(4x-2)/5 | | (3x-1)/4=4x-2/5 | | C=2(6f-32) | | −7=−6−1/5x | | 3+d+-5=10 | | C=2(3f-32) | | 4(3x+-1)=24 | | 6x-15=6x-11 | | 9-12y=-14 |